PELATIHAN PENCATATAN KEUANGAN PADA UMKM DI DESA GEBANG BUNDER KECAMATAN PLANDAAN JOMBANG - Dwi Ari Pertiwi; Rachma Agustina; Meta Ardiana; Deasy Ervina (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of community service from the Accounting Study Program Team of the Faculty of Economics, Hasyim Asy’ari University of Tebuireng, Jombang to UMKM in Gebang Bunder, Plandaan, Jombang is to provide solutions of problems which is faced by UMKM related to a lack of knowledge of financial records. The form of service is a training on recording of financial reports as to produce a financial report. The training was held by luring at the Gebang Bunder village hall. The material is about the financial recording which the form is an accounting cycles consists of identification and analysis of transactions, journals, ledgers, trial balances, adjusting journals, trial balances after adjusments, financial reports, closing journals, trial balances after closing and reversing journals. The results of the community service are expected that UMKM understand and can apply financial records correctly in their business.Keywords: Training, Financial Record, UMKM